Livelihood vulnerability and resilience of rainfed rice farmers to climate change in Java, Indonesia - ZUHUD ROZAKI; RIFKA DIAH SAPUTRI; MOHD FAUZI KAMARUDIN; NUR RAHMAWATI (Asian Journal of Agriculture, 2026)
Abstract. Rozaki Z, Saputri RD, Kamarudin MF, Rahmawati N. 2026. Livelihood vulnerability and resilience of rainfed rice farmers to climate change in Java, Indonesia. Asian J Agric 10 (1): g100108. https://doi.org/10.13057/asianjagric/ g100108. Climate change, characterized by altered rainfall patterns, rising temperatures, prolonged droughts, and increasing pest infestations, poses significant challenges for rain-fed rice farmers who heavily depend on rainfall. This study assesses and compares the resilience of rainfed rice farmers in Central Java (Klaten, Karanganyar, Boyolali, and Wonogiri) and Yogyakarta (Gunungkidul and Bantul), Indonesia, using the Livelihood Vulnerability Index (LVI). The research involved 300 respondents from six districts, selected through purposive sampling, with data collected via structured household interviews covering social, economic, physical, environmental, and institutional indicators. The LVI was constructed by normalizing indicators and aggregating them into exposure, sensitivity, and adaptive capacity dimensions using a weighted average approach. The results reveal moderate adaptive capacity in both provinces (A=0.36 in Central Java and 0.39 in Yogyakarta), with overall vulnerability classified as medium (LVI=0.40 and 0.46, respectively). However, the primary drivers of vulnerability vary across regions. In Central Java, education level (p=0.001) and household size (p=0.008) significantly influence vulnerability, indicating that limited human capital and higher dependency ratios increase sensitivity to climate shocks. In contrast, farming experience is the dominant factor in Yogyakarta (p=0.010), indicating that long-term reliance on traditional practices may limit adaptive responses to changing climatic conditions. These comparative findings highlight that vulnerability in rainfed rice systems is shaped not only by climatic exposure but also by region-specific socioeconomic factors. Accordingly, climate-responsive agricultural policies should be tailored to different regions, emphasizing improved extension services, access to climate and market information, adaptive training, and livelihood diversification to enhance the resilience of rainfed rice farmers.